1994
DOI: 10.1111/j.1532-950x.1994.tb00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Effects of Four Opioid‐Tranquilizer Combinations in Dogs

Abstract: The cardiorespiratory effects of four opioid-tranquilizer combinations were evaluated in six dogs. The four combinations were administered to each dog in a randomized order. Buprenorphine (BUP; 0.01 mg/kg IV) or oxymorphone (OXY; 0.1 mg/kg IV) was followed in 10.4 +/- 1.3 minutes by midazolam (MID; 0.3 mg/kg IV) or acepromazine (ACE; 0.05 mg/kg IV). Nalbuphine (0.16 mg/kg IV) was administered 94.1 +/- 2.3 minutes after the tranquilizer was given. Heart rate (HR) and mean arterial blood pressure (MAP) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…Jacobson et al. demonstrated that combined administration of buprenorphine and acepromazine did not induce significant changes in arterial carbon dioxide tension (PCO 2 ) or oxygen tension (PO 2 ) in dogs 8 . Stepien et al.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobson et al. demonstrated that combined administration of buprenorphine and acepromazine did not induce significant changes in arterial carbon dioxide tension (PCO 2 ) or oxygen tension (PO 2 ) in dogs 8 . Stepien et al.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Similar to hypoxemia, hypercarbia is difficult to detect on the basis of physical signs alone. Frequently, pure opioid agonists are used perioperatively for analgesia in dogs, and most pure opioid agonists cause respiratory depression and hypercarbia.…”
mentioning
confidence: 99%
“…It is unclear whether changing plasma concentrations of buprenorphine and/or acepromazine after bolus administration might affect the breathing pattern of animals. However, we assume that the use of buprenorphine (0.01 mg/kg) and acepromazine (0.05 mg/kg) did not have a major effect on the results of the present study, because respiratory variables stayed within reference limits following their administration at these doses to dogs 16,23 …”
Section: Discussionmentioning
confidence: 74%